2012
DOI: 10.1097/yco.0b013e3283556c63
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative care for depression in medically ill patients

Abstract: Collaborative care interventions are efficacious in medically ill patients with depression. However, there is no data concerning their cost-effectiveness. Furthermore, as trials on collaborative care comprise a heterogeneous set of components, the most effective characteristics should be identified. Moreover, these interventions should be adapted to other healthcare systems than the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Literature reviews to date have focused on the effectiveness of CC for psychological outcomes, rather than for physical outcomes, in patients with comorbid physical conditions 5 and depressive or anxiety disorders [30][31][32]. Therefore, the objective of this study was to perform a systematic review and meta-analysis that extends beyond previous reviews by reporting the effects of CC on physical disorders and co-morbid depressive or anxiety disorders, with a primary focus on physical outcomes and illness burden.…”
Section: Objectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature reviews to date have focused on the effectiveness of CC for psychological outcomes, rather than for physical outcomes, in patients with comorbid physical conditions 5 and depressive or anxiety disorders [30][31][32]. Therefore, the objective of this study was to perform a systematic review and meta-analysis that extends beyond previous reviews by reporting the effects of CC on physical disorders and co-morbid depressive or anxiety disorders, with a primary focus on physical outcomes and illness burden.…”
Section: Objectivesmentioning
confidence: 99%
“…In such cases of comorbidity, the treatment response is often less favourable for both the chronic medical condition [21] and the mental disorder [22][23][24]. Research has shown that CC is effective, as compared to CAU, in improving depressive and anxiety disorders [25][26][27][28][29][30][31][32][33], and the National Institute for…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…The presence of comorbid physical diseases is among the important risk factors for poor outcomes in MDD, and MDD is highly prevalent in patients with various medical conditions. Twenty-five per cent of patients with cancer, one-third of patients with Alzheimer's disease, and half of patients with Parkinson's disease have major depression, rendering MDD a potential cause of poor prognosis in such conditions [26,27].…”
Section: Chronic Physical Diseases Plus Major Depressive Disordermentioning
confidence: 99%